Sistem Diagnosis Penyakit Mata Menggunakan Metode Fuzzy Tsukamoto - Galih Putra Suwandi; Nurul Hidayat; Suprapto Suprapto (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Eye is one of the five most important senses which include hearing, smell, taste, and touch. In the eye itself, there are various kinds of diseases. According to the Basic Health Research (Riskendas) on 2013, they collected the data of blindness with the respondents analyzed totaling 224,714,112 people, and experiencing blindness 966,329 people. Blindness is one of several eye diseases such as conjunctivitis, anterior uveitis, cataracts and others. Due to many types of eye diseases, a system is needed to take and apply knowledge from experts. It is Fuzzy Tsukamoto method. This method is chosen because it has more advantages, that have data tolerance and are very flexible, and are intuitive and can provide qualitative. The results of the implementation and testing found 85% accuracy in conjunctivitis, 85% for uveitis anterior, 90% for cataracts and 86.67% for the average accuracy of the three diseases.